(untitled) (American International Journal of Economics and Finance Research, 2022)
This study investigates the impact of financial stability on economic growth in Nigeria by employing the Autoregressive Distributed Lag (ADRL) technique using time series data from Q1, 2006-Q4, 2020. Real GDP is the experimental variable and proxy for economic growth, while financial stability is measured by capital adequacy, non-performing loans, liquidity ratios and return on assets of the banking sector as well as the All-share Index of the stock market. The results indicate that capital adequacy, non-performing loans and liquidity ratios impact negatively on economic growth. The All-share Index, however, reveals a positive and significant relationship with growth. The implication is that financial stability policy needs to be complemented by other financial development objectives in order to stimulate economic growth. The data utilised for the study is limited to the banking sector and the capital market, which dominate the financial sector in Nigeria. The study contributes to existing research as it offers new insight into the relationship between key measures of financial stability and economic growth in Nigeria considering that few studies have been carried out in this area. It established a negative relationship between financial stability and economic growth in Nigeria. JEL Classification Codes: E44, G20, O40.